2007
DOI: 10.1021/jp063315v
|View full text |Cite
|
Sign up to set email alerts
|

Removal of NO in NO/N2, NO/N2/O2, NO/CH4/N2, and NO/CH4/O2/N2 Systems by Flowing Microwave Discharges

Abstract: In this paper, continuing previous work, we report on experiments carried out to investigate the removal of NO from simulated flue gas in nonthermal plasmas. The plasma-induced decomposition of small concentrations of NO in N2 used as the carrier gas and O2 and CH4 as minority components has been studied in a surface wave discharge induced with a surfatron launcher. The reaction products and efficiency have been monitored by mass spectrometry as a function of the composition of the mixture. NO is effectively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Removal of NOx was also studied by using pulsed corona discharge [6][7][8][9][10][11][12][13] and microwave discharge methods [14][15][16][17][18][19][20][21][22][23]. Discharge methods will become a low cost convenient method, if NOx can be removed without using any catalysts and reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of NOx was also studied by using pulsed corona discharge [6][7][8][9][10][11][12][13] and microwave discharge methods [14][15][16][17][18][19][20][21][22][23]. Discharge methods will become a low cost convenient method, if NOx can be removed without using any catalysts and reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Baeva et al [234,235] also found the same phenomenon when he decomposed NO x by pulsed microwave discharge plasma at atmospheric pressure. Hueso et al [236,237] used microwave-induced plasma to study the decomposition of NO in Ar and N 2 . In the presence of oxygen, if enough reductive gases were added, the decomposition of NO was still dominant.…”
Section: Direct Decomposition Of No X By Plasmamentioning
confidence: 99%
“…Further research is still necessary to implement disruptive improvements that can pave the way for the regular use of solar light and/or low consumption artificial lights (i.e. Light-emitting diodes-LEDs, novel reactor configurations and so on) [9,10,[12][13][14][16][17][18][19][20][21][22][23][24][25]. In addition, it is also necessary to boost the development of novel photocatalytic materials that can overcome the inherent burdens of TiO2 and are able to take advantage of the full solar spectrum instead of the limited UV range attributed to TiO2 [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%